Salt reduction in bread: Is it enough? Preliminary results of a HIA in Portugal. (13th November 2019) - Santos, J; Braz, P; Costa, A; Costa, L; Santos, M; Brazão, R; Alves, J; Lopes, I; Guerreiro, A; Almeida, T
Abstract: Issue: Health Impact Assessment (HIA) is a methodology that aims at assessing the impact of policies in health. A pilot HIA is in progress to kick off the implementation of this methodology in Portugal with the support of the World Health Organization (WHO). In this context, the impact of a nation-wide policy that intends to achieve a maximum of 1 g of salt/100 gr in bread is under assessment. Description of the issue: In 2017, Portugal approved a protocol between the industry and other stakeholders to gradually decrease the amount of salt in bread, as this is the main source of salt intake. The purpose of this study was to assess the impact in blood pressure from current (1.4 gr) to 1 g (29% reduction) of salt in bread. Data from two different surveys regarding blood pressure and salt intake was gathered. We estimated the decrease in blood pressure with respect to current average values according to sex, age, education and region. Results: It is expected that a reduction of 29% in salt intake through bread contributes to a general decrease in systolic pressure for normotensive people (from 120.4mmHg to 120.0mmHg, p = 0.85) and hypertensive people (from 151.0mmHg to 150.1mmHg, p = 0.68), although not statistically significant. Older hypertensive individuals (65 to 75 years) are the group with the largest benefit (152.8mmHg to 152.0mmHg) but no statistical difference was found. Disaggregation by sex, region and education also didn't show any statistical difference. Lessons: The impact in blood pressure from a 29% reduction in salt intake from bread seems very small. We found no statistical significance between the current and expected values in blood pressure either for total or group stratification. The absence of statistical effect might be due to sample size as our sources only allowed us to work with aggregated data. Key messages: Quality and access to data is needed to assess impact of policies. to increase effects in blood pressure either salt reduction from bread must be larger or a wider range of products should be considered.